Incidence and frequency of nondental incidental findings on cone-beam computed tomography. Issue 9 (September 2016) - Togan, Benjamin; Gander, Thomas; Lanzer, Martin; Martin, Rücker; Lübbers, Heinz-Theo
Abstract: Purpose: The purpose of the present study was to determine the frequency of relevant nondental related incidental findings in cone-beam computed tomography (CBCT) of the head and neck. Material and methods: Nine hundred ninety-nine images were retrospectively reviewed for incidental findings. Those were defined as carotid artery calcification (CAC), paranasal sinus findings (PSF), sialolithiasis of the parotid gland (SP) or submandibular gland (SSub), calcification of the ligamentum stylohyoideum (CLS), and Stafne bone cavity (SBC). All datasets obtained between 2010 and 2014 at a university-based school of dental medicine in Switzerland were reviewed. Demographic data such as age and sex were also recorded. Results: A total of 350 incidental findings within the 999 CBCT scans were identified. The most frequent finding was PSF (27.8%), followed by CLS (11.6%), CAC (5.3%), and SSub (0.8%). No SP or SBC was found. Incidental findings were most frequent between 61 and 70 years of age. Males had a higher prevalence in CAC, PSF, and SSub than females. Conclusions: These results underscore the need for a complete examination of every CBCT image beyond the region of interest.